Evaluation of the tolerance and forage quality of different ecotypes of seashore paspalum - Jiang, Kai; Yang, Zhimin; Sun, Juan; Liu, Huancheng; Chen, Shenmiao; Zhao, Yongzhuo; Xiong, Wangdan; Lu, Wenjie; Wang, Zeng-Yu; Wu, Xueli (Frontiers in Plant Science, 2022)
Seashore paspalum is a halophytic, warm-season grass with wide applications. It is noted for its superior salt tolerance in saline environments; however, the nutritive value of seashore paspalum and the effect of salinity remains to be determined. Therefore, this study aimed to evaluate the relationship between agronomic traits and forage quality and identified the effects of short-term high-salt stress (1 week, 700 mM NaCl) on the growth and forage nutritive value of 16 ecotypes of seashore paspalum. The salt and cold tolerances of the seashore paspalum ecotypes were assessed based on the survival rate following long-term high-salt stress (7 weeks, 700 mM NaCl) and exposure to natural low temperature stress. There were significant genetic (ecotype-specific) effects on plant height, leaf–stem ratio, and survival rate of seashore paspalum following salt or low temperature stress. Plant height was significantly negatively correlated with the leaf–stem ratio (r = −0.63, P<0.01), but the heights and leaf–stem ratios were not significantly correlated with the fresh weight (FW) and dry weight (DW) of the shoots. High salinity decreased the FW and DW of the shoots by 50.6% and 23.6%, respectively, on average. Seashore paspalum exhibited outstanding salt tolerance and forage quality at high salinity. The survival rate of the different ecotypes of seashore paspalum varied from 6.5% to 49.0% following treatment with 700 mM NaCl for 7 weeks. The crude protein (CP) content of the control and treatment groups (700 mM NaCl) was 17.4% and 19.3%, respectively, of the DW on average, and the CP content of most ecotypes was not significantly influenced by high salinity. The average ether extract (EE) content ranged from 4.6% to 4.4% of the DW under control and saline conditions, respectively, indicating that the influence was not significant. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of the control group were 57.4% and 29.8%, respectively, of the DW on average. Salt stress reduced the content of NDF and ADF to 50.2% and 25.9%, respectively, of the DW on average. Altogether, the results demonstrated that stress did not have any significant effects on the CP and EE content of most ecotypes, but reduced the NDF and ADF content and improved relative feed value (RFV). The results obtained herein support the notion that seashore paspalum is a good candidate for improving the forage potential of saline soils and can provide useful guidelines for livestock producers.